Antennal olfactory responses of adult meadow spittlebug, Philaenus spumarius, to volatile organic compounds (VOCs). - Giacinto, Salvatore Germinara (Public Library of Science (PLoS), 2018)
The meadow spittlebug, Philaenus spumarius L. (Hemiptera, Aphrophoridae) is a commonly found vector of Xylella fastidiosa Wells et al. (1987) strain subspecies pauca associated with the "Olive Quick Decline Syndrome" in Italy. To contribute to the knowledge of the adult P. spumarius chemoreceptivity, electroantennographic (EAG) responses of both sexes to 50 volatile organic compounds (VOCs) including aliphatic aldehydes, alcohols, esters, and ketones, terpenoids, and aromatics were recorded. Measurable EAG responses were elicited by all compounds tested. In both sexes, octanal, 2-octanol, 2-decanone, (E)-2-hexenyl acetate, and vanillin elicited the strongest antennal amplitude within the chemical groups of aliphatic saturated aldehydes, aliphatic alcohols, aliphatic acetates and aromatics, respectively. Male and female EAG responses to sulcatol, (±)linalool, and sulcatone were higher than those to other terpenoinds. In both sexes, the weakest antennal stimulants were phenethyl alcohol and 2-pentanone. Sexual differences in the EAG amplitude were found only for four of test compounds suggesting a general similarity between males and females in antennal sensitivity. The olfactory system of both sexes proved to be sensitive to changes in stimulus concentration, carbon chain length, and compound structure. Compounds with short carbon chain length (C5-C6) elicited lower EAG amplitudes than compounds with higher carbon chain length (C9-C10) in all classes of aliphatic hydrocarbons with different functional groups. The elucidation of the sensitivity profile of P. spumarius to a variety of VOCs provides a basis for future identification of behaviorally-active compounds useful for developing semiochemical-based control strategies of this pest.